The Dismissal of Constitutional Court Judges by the House of Representatives from the Perspective of Separation of Powers - Rama Satria (Jurnal Mengkaji Indonesia, 2025)
Abstract: The power of the House of Representatives to remove constitutional judges is discussed and analyzed in this article. It examines how the House of Representatives carries out its oversight role and if that includes assessing constitutional judges. The House of Representatives' dismissal of constitutional judges is also demonstrated by actual examples in this article. Purpose: From the perspective of the separation of powers, this research aims to investigate and evaluate the House of Representatives' action in dismissing constitutional judges. Design/Methodology/Approach: A legislative, conceptual, and case approach using a legal research technique is employed in this analysis. Primary and secondary legal resources constitute the legal materials utilized. Findings: The findings of this investigation demonstrate that the DPR lacks the authority to fire Constitutional Court judges, regardless of whether it be via an evaluation or via any other method. Constitutional Court judges, who are chosen and appointed by the President, must continue in their role until their term expires, unless they are no longer qualified as per the Law on the Constitutional Court. The model of DPR supervision of Constitutional Court Judges, as described in Article 228A of DPR Regulation No. 1 of 2025, is unconstitutional. The oversight model violates the 1945 Indonesian Republic Constitution, the Constitutional Court Law, Constitutional Court Decision 103/PUU-XX/2022, the separation of powers, the lawmaking, independence, and authority principles. Originality/value: This research is highly original and innovative. This is because the author explores the issue from the perspective of separation of powers. The findings of this article contribute to the implementation of constitutional judges' independence.